Modus Operandi, Penyebab, dan Dampak Tindak Pidana Perjudian Online yang Dilakukan oleh Mahasiswa di Daerah Istimewa Yogyakarta - Witri Naeli Ginaniar; Wahyu Priyanka Nata Permana (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to analyze online gambling crimes committed by university students in the Special Region of Yogyakarta from a criminological perspective. The research focuses on modus operandi, causal factors, and resulting impacts. The method used is empirical legal research with a sociological and criminological approach. Data were collected through literature review and interviews. The findings show that the modus operandi includes promotion via social media, gambling applications, and deposit-based transactions. The main contributing factors are social influence, economic needs, and weak oversight. Online gambling has negative impacts on students’ psychological condition, finances, and moral integrity. The study recommends preventive efforts through education and strengthened institutional roles.